World economy and international business theories, trends, and challenges - Bulatov, Alexander (Cham, Switzerland Springer, 2023)
This textbook offers a comprehensive picture of the world economy, the global business environment, and international business. The book is divided into three parts, the first of which introduces readers to the essentials of the world economy, including its typology, key concepts and theories, the dynamics of the world economy, and key actors and institutions. It also addresses macroeconomic and financial indicators for economic growth and forecasting and discusses major modern trends and problems, such as the Fourth Industrial Revolution, patterns of globalization, shifts in global economic power, and developmental, social and environmental challenges. In turn, the second part focuses on the global business environments, presenting country and regional studies. The third part addresses macro and micro aspects of international business, featuring contributions on topics such as global economic governance, global capital flows, multinational corporations, global value chains, international trade and its regulation and practice, international knowledge transfer, international labor migration as well as foreign aid, external debt, and business culture in international business.
Contents - World and Global Economy - - World and Global Economy, Global Business Environment, and International Business: Nature, Formation, and Structure - - Concepts and Theories of Global Economy - - World Economy: Growth, Proportions, Efficiency, and Forecasting - - World Economy Major Trends: New Normal, The Fourth Industrial Revolution, Globalization, Sustainable Development - - World Economy Major Trends: Evolution of National Economic Systems - - World Economy Major Trends: International Economic Integration - - Resources of World Economy: Human Capital - - Resources of World Economy: Real Capital - - Resources of World Economy: Financial Capital - - Resources of World Economy: Natural Resources - - Global Challenges: Environment - - Global Challenges: Backwardness and Modernization - - Global Challenges: Social Problems - - Global Business Environment: Countries and Regions - - Developed Economies as a Group - - USA - - European Union - Developed Economies of Asia - - Less-Developed Economies as a Group - - China - - India - - Southeast Asia - - The Near and Middle East - - Latin America - - Sub-Saharan Africa - - Russia and Other Post-Soviet Economies - - International Business: Macro and Micro Aspects - - Balance of Payments - - Global Economic Governance and International Economic Organizations - - Global Capital Flows - - Multinational Enterprises - - Global Value Chains - - Global Financial Market - - International Trade in Goods and Services - - Multilateral Trading System and Global Trade Regulation - - World Markets of Goods and Services - - Marketing in Global Business - - International Trade Purchase and Sale Transactions - - International Settlements and Payments, Global Foreign Exchange Market - - International Knowledge Transfer - - International Labour Migration - - Foreign Aid - - External Debt - - Business Cultures in International Business.
Keywords: International economic relations; Economics; International business enterprises